2015
DOI: 10.1002/anie.201507848
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Copper‐Catalyzed Quinoline Alkynylation

Abstract: A highly enantioselective copper-catalyzed alkynylation of quinolinium salts is reported. The reaction employs StackPhos, a newly developed imidazole-based chiral biaryl P,N ligand, and copper bromide to effect a three-component reaction between a quinoline, a terminal alkyne, and ethyl chloroformate. Under the reaction conditions, the desired products are delivered in high yields with ee values of up to 98 %. The transformation tolerates a wide range of functional groups with respect to both the alkyne and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 75 publications
0
70
0
Order By: Relevance
“…Aponick et al developed an enantioselective copper‐catalyzed alkynylation of quinolines, which were again activated towards the addition by acylation (using ethyl chloroformate in this case), which they showcased in a synthesis of the Hancock alkaloids. Treatment of quinoline 8 with ethyl chloroformate, n ‐propylacetylene, CuBr and ( S )‐StackPhos 76 gave 1,2‐dihydroquinoline derivative 77 in 62 % yield and 92 % ee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aponick et al developed an enantioselective copper‐catalyzed alkynylation of quinolines, which were again activated towards the addition by acylation (using ethyl chloroformate in this case), which they showcased in a synthesis of the Hancock alkaloids. Treatment of quinoline 8 with ethyl chloroformate, n ‐propylacetylene, CuBr and ( S )‐StackPhos 76 gave 1,2‐dihydroquinoline derivative 77 in 62 % yield and 92 % ee.…”
Section: Discussionmentioning
confidence: 99%
“…Takemoto et al [36] reported a method to effect enantioselective addition of a range of styrylboronic acid derivatives to a range of quinoline derivatives (Petasis-type reaction), which they applied to the ides was reported by Wei, Wang, et al [37] who applied this transformation to enable the synthesis of Hancock alkaloids. Under their optimized conditions, reaction of N-methylquinolinium iodide 71 with (E)- Aponick et al [38] developed an enantioselective copper-catalyzed alkynylation of quinolines, which were again activated towards the addition by acylation (using ethyl chloroformate in this case), which they showcased in a synthesis of the Hancock Scheme . C(2)-Functionalization of 1,2,3,4-Tetrahydroquinoline.…”
Section: Introductionmentioning
confidence: 99%
“…With the goal of developing an enantioselective chromone alkynylation, we set out to explore the proposed transformation using our Stack ligands . These ligands were designed to have a stabilizing intramolecular catalyst–catalyst interaction between the naphthyl and C 6 F 5 groups, and the groups on the backbone were originally incorporated to establish a chiral pocket with quadrants of differing steric demand . The backbone aryl groups can be modified to include electron‐withdrawing/donating substituents and we sought to determine if these modifications could impact the reaction, possibly by intermolecular π–π or π–cation interactions.…”
Section: Methodsmentioning
confidence: 99%
“…[23] Studies from our laboratory have been directed at using heterocyclic chiral biaryl ligands in enantioselective transformations [24][25][26][27][28][29] and we postulated that our Stack ligands might also control other types of selectivity. [23] Studies from our laboratory have been directed at using heterocyclic chiral biaryl ligands in enantioselective transformations [24][25][26][27][28][29] and we postulated that our Stack ligands might also control other types of selectivity.…”
mentioning
confidence: 99%
“…With the goal of developing am ethod to couple these alkyne reactivities in an efficient one-pot transformation, it was recognized that both reaction and ligand selection would be crucial, and although chiral ligands are most commonly used for enantioselectivity,t hey can also efficiently control other types of selectivity. [23] Studies from our laboratory have been directed at using heterocyclic chiral biaryl ligands in enantioselective transformations [24][25][26][27][28][29] and we postulated that our Stack ligands might also control other types of selectivity. We recently reported conjugate addition to Meldrumsa cid derivatives in water, [30] and we decided that this would be asuitable reaction platform from which to build asubsequent catalytic transformation to form the six-membered lactone 7.…”
mentioning
confidence: 99%